2015
DOI: 10.1186/s12906-015-0640-5
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin alters the expression profiles of MicroRNAs in BxPC-3 human pancreatic cancer cells

Abstract: BackgroundOridonin, an ingredient used in traditional Chinese medicine, has been demonstrated to play an important role in antitumour effects, but the mechanism underlying its antitumour properties is still not clear.MethodsTo verify the anti-cancer effects of oridonin via a miRNA-dependent mechanism, comprehensive miRNA expression profiling of oridonin-treated BxPC-3 human pancreatic cancer cells was performed using a miRNA microarray assay based on Sanger miR-Base Release 20, followed by a validation using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…The majority of them (19 DEMs) have been either verified to be associated with PC with the HMDD and miR2Disease databases or found to be differentially expressed in PC based on the Pancreatic Cancer Database (PCD) and TCGA. The rest DEMs were found to be differentially expressed in a recent study on human pancreatic cancer cells, especially hsa‐miR‐216b‐3p, hsa‐miR‐196b‐5p, hsa‐miR‐2114‐5p, and hsa‐miR‐216a‐3p whose expression level changes identified here were consistent with previous observations. This suggests that our results agree well with previous findings.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of them (19 DEMs) have been either verified to be associated with PC with the HMDD and miR2Disease databases or found to be differentially expressed in PC based on the Pancreatic Cancer Database (PCD) and TCGA. The rest DEMs were found to be differentially expressed in a recent study on human pancreatic cancer cells, especially hsa‐miR‐216b‐3p, hsa‐miR‐196b‐5p, hsa‐miR‐2114‐5p, and hsa‐miR‐216a‐3p whose expression level changes identified here were consistent with previous observations. This suggests that our results agree well with previous findings.…”
Section: Resultssupporting
confidence: 91%
“…DEMs were found to be differentially expressed in a recent study on human pancreatic cancer cells, 63 especially hsa-miR-216b-3p, hsa-miR-196b-5p, hsa-miR-2114-5p, and hsa-miR-216a-3p whose expression level changes identified here were consistent with previous observations. This suggests that our results agree well with previous findings.…”
Section: Analysis Of Differentially Expressed Mirnassupporting
confidence: 91%
“…In our previous study, we found that oridonin alters the expression profiles of miRNAs in the BxPC-3 human pancreatic cancer cells, 105 miRNAs were significantly altered: 49 miRNAs were significantly downregulated, while 56 were significantly upregulated. Among them, miR-200b-3p was significantly downregulated (19), and also significantly downregulated in the PANC-1 cells (Fig. 1C).…”
Section: Discussionmentioning
confidence: 91%
“…A previous microarray study has shown that 105 miRNAs are differentially expressed in BxPC-3 cells treated with oridonin at concentrations of 0 and 87.8 µM (19). As shown in Fig.…”
Section: Oridonin Treatment Alters Mir-200b-3p Expression In Bxpc-3 Amentioning
confidence: 81%
“…The diterpenes are multiedged swords in their activities. Dysoxydensin B, C and E isolated from Dysoxylum densiflorum exhibited a moderate cytotoxic effect on a number of human cancer cell lines (Gu et al , ), while oridonin is evident to inhibit the cell growth, probably via regulating the expression of miRNAs in BxPC‐3 human pancreatic cancer cells (Gui et al , ).…”
Section: Diterpenic Anticancer Traitsmentioning
confidence: 99%